12.5.3 Pneumatic circuit for bi-directional speed control of a single-acting cylinder - M.Galal Rabie (McGraw-Hill's AccessEngineering., 2024)
Bi-Directional Speed Control of a Single-Acting Cylinder. The airflow in and out of the cylinder is restricted by two pre-set throttles, ensuring controlled speed in both directions